Gunnhildur and the male whores - Jóna Guðbjörg Torfadóttir (Universität Tübingen, 2004)
The Queen mother Gunnhildr is one of the most evil Norwegian female characters in the Middle ages. She appears in many old stories where she is usually the female agent for ill in the sagas; she is wicked, promiscuous and very often skilled in magical arts. The purpose of this paper is to focus on how the medieval writers treat Gunnhildr, the sources about her, historical and fiction, and most of all her relationship with Icelandic farmers. Gunnhildr is a 'tröll', for in Old Icelandic the word meant a being skilled in magical arts, and she is treated as one. The descriptions of her are usually very exaggerated and fantastic and they remind one of the adventurous troll women, especially the evil stepmother. In most of the sagas the origins of Gunnhildr lie in Finnmark, a symbolic Útgarðr from which she draws a seductive strength, sexual liaison and magic. Gunnhildr charms the king and corrupts the kingdom and not before long she is the ruler of Norway. Gunnhildr has no stepchildren but she seduces young men to have sexual relationships with her and she is old enough to be the mother of at least some of them. Another parallel to Gunnhildr is the Saami, which is literally and figuratively located in the Beyond, i.e. Finnmark. This is prominent in Egils saga Skallagrímssonar. Gunnhildr and Egill have many things in common; they have a similar background and they are both foreigner and opponent in the Norwegian kingdom. But even though Gunnhildr is unpopular among the Norwegian people she is their queen and Egill is a courtier, in her service. Despite their different position Egill constantly shows her male chauvinism. He never addresses her and barely mentions her in his poetry. Gunnhildr´s origin in the northern wilderness seems to be a false report and most scholars have thought the narrative in Historia Norwegiæ closer to the truth. This history of Norwegian kings was written in Latin around 1150-1200 and is the only source, which tells of Gunnhild´s Danish origin; she is the daughter of the royal couple Gorm and ...